Assessment of buccal bone thickness of aesthetic maxillary region in Nepalese adults: A Cone Beam Computed Tomography (CBCT) Study - Shrestha, Bidhan; Kurtzman, GM; Basnet, BB; Adhikari, G; Rokaya, D (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: The dental implant has now become a routine treatment for oral rehabilitation. The treatment planning and positioning of implants is greatly dependent upon the clinicians’ understanding of the alveolar architecture of the maxilla and mandible. In the esthetic zone, the implants therapy can be successful only if it is in harmony with the surrounding tissues. Objectives: To study the labial osseous wall thickness of the anterior maxillary bone at various sites apical to the cemento-enamel junction using the cone beam computed tomography (CBCT). Materials and Methods: Cone beam tomographic scans of 150 Nepalese adults (70 females and 80 males) were obtained from the Oral Radiology Unit, Kantipur Dental College Teaching Hospital & Research Center. CBCT scans were carried out by trained technicians using CS 9300 (Carestream Dental, Atlanta, GA, USA). In the CBCT images, distances between the CEJ and alveolar crest (AC) as well as the labial bone thickness at different levels (at the crest, 1mm, 3mm and 5 mm) were measured for central incisor (CI), lateral incisor (LI), and canine (C). Results: It showed that the average distance between CEJ and crest of CI, LI, and C were 1.98±0.84 mm, 2.09±0.83 mm, and 2.12±1.20 mm, respectively. Only 3.3% of the CI, 10.7% of the LI, and 13.3% of the C showed a thick labial bone (1–2 mm) at the crestal level. At the 1 mm level, 75.3% of the CI, 64.5% of LI, and 70% C showed a very thin bony wall. Similarly, none showed very thick bony wall (>2mm). The thickness level was significant at the crest and at 5 mm level. The highest bone thickness of LI was found at the 1 mm level. In addition, there was also significant difference in different levels of LIs. The mean distance between the CEJ and the AC for the CI and the C was significantly higher in males than females. Conclusion: The labial bone in the anterior maxilla is inherently thin, with more than 80% of the sites showing less than 1 mm. The results of this study may be useful for the implant planning in the esthetic zone and it is recommended tissue augmentation (soft and hard) to achieve esthetic emergence profile.